Pengembangan Mobile Learning Berbasis Android pada Materi Perkalian antara Dua Matriks bagi Siswa Kelas X di SMK Satya Bhakti 1 Jakarta - Fadillah Al Amin; Pinta Deniyanti; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2022)
This study aims to develop Android-based mobile learning on the multiplication material between two matrices for class X students of SMK Satya Bhakti 1 Jakarta. Mobile learning is made as an alternative learning media that can be used when learning online. This is because pre-existing learning media are considered less attractive and this mobile learning can be used without quota. This research is development research. The procedures in this study consisted of analyzing the developed product, developing the initial product, and testing the product. The results showed that the Android-based mobile learning developed was feasible to use. The results of media validation were 75.90% and material and language validations were 77.36%. The results of the trials on teachers were 82.35%. The small-scale trial results were 84.77%. The results of large-scale trials were 83.19%. Based on these results, it was concluded that Android-based mobile learning on the multiplication material between two matrices for class X students of SMK Satya Bhakti 1 Jakarta was feasible.